Multimodal regulation of encystation in Giardia duodenalis revealed by deep proteomics. Issue 10 (September 2021) - Balan, Balu; Emery-Corbin, Samantha J.; Sandow, Jarrod J.; Ansell, Brendan Robert E.; Tichkule, Swapnil; Webb, Andrew I.; Svärd, Staffan G.; Jex, Aaron R.
Graphical abstract: Highlights: First complete observation of encystation at the proteomic level up to mature cyst. Reproducibly identified 3863 (64%) and quantified 3382 proteins (56%) of Giardia annotated proteome across encystation. One-third (1169 proteins) of the quantified proteome is differentially expressed in mature cysts relative to trophozoites. Transcriptome-proteome correlation of trophozoites and cysts showed evidence of post-transcriptional regulation. Encystation is mechanistically complex and tightly regulated. Abstract: Cyst formation in the parasitic protist Giardia duodenalis is critical to its transmission. Existing proteomic data quantifies only 17% of coding genes transcribed during encystation and does not cover the complete process from trophozoite to mature cyst. Using high-resolution mass spectrometry, we have quantified proteomic changes across encystation and compared this with published transcriptomic data. We reproducibly identified 3863 (64.5% of Giardia proteins) and quantified 3382 proteins (56.5% of Giardia proteins) over standard trophozoite growth (TY), during low-bile encystation priming (LB), 16 h into encystation (EC), and at cyst maturation (C). This work provides the first known expanded observation of encystation at the proteomic level and triples the coverage of previous encystation proteomes. One-third (1169 proteins) of the quantified proteome is differentially expressed in the mature cyst relative to the trophozoite, including proteasomal machinery, metabolic pathways, and secretory proteins. Changes in lipid metabolism indicated a shift in lipid species dependency during encystation. Consistent with this, we identified the first, putative lipid transporters in this species, representing the steroidogenic acute regulatory protein–related lipid transfer (StARkin), oxysterol binding protein related protein (ORP/Osh) and glycosphingolipid transfer protein (GLTP) families, and follow their differential expression over cyst formation. Lastly, we undertook correlation analyses of the transcriptome and proteome of trophozoites and cysts, and found evidence of post-transcriptional regulation of key protein classes (RNA binding proteins) and stage-specific genes (encystation markers) implicating translation-repression in encystation. We provide the most extensive proteomic analysis of encystation in Giardia to date and the first known exploration across its complete duration. This work identifies encystation as highly coordinated, involving major changes in proteostasis, metabolism and membrane dynamics, and indicates a potential role for post-transcriptional regulation, mediated through RNA-binding proteins. Together our work provides a valuable resource for Giardia research and the development of transmission-blocking anti-giardials.